The role of colonoscopy in the management of intestinal obstruction: a 20-year retrospective study - Christodoulou Dimitrios K; Ignatiadou Eleftheria; Tatsioni Athina; Maliouki Mariana; Katsanos Konstantinos H; Fatouros Michael; Tsianos Epameinondas V (BMC Gastroenterology, 2010)
Abstract Purpose The aim of the study was to assess the use colonoscopy over time in the assessment of large bowel obstruction in a tertiary university hospital. Methods Retrospective analysis of surgical and colonoscopy records for the years 1990-2009 in a university hospital. All patients diagnosed with non-conservatively managed bowel obstruction were included. Results We recorded 644 patients diagnosed with non-conservatively managed bowel obstruction. Four hundred forty-one (67.3%) were managed only by surgery, 157 (23.6%) were managed by colonoscopy, and 46 (6.9%) by combined colonoscopy and surgery. Patients over 77 years were more likely to receive colonoscopy as monotherapy or combined with surgery as compared to younger patients. Management by colonoscopy only and by combined colonoscopy and surgery increased over time. Conclusions Colonoscopy in the management of non-conservatively treated bowel obstruction increased over time. However, therapeutic colonoscopy still has a limited role in bowel obstruction either as monotherapy or combined with surgery.